Neurovirulence, viscerotropism and immunogenicity of live attenuated yellow fever 17D vaccine virus in non-human primates. Issue 3 (16th January 2023) - Tyagi, Parikshit; Ganguly, Milan; Manney, Satyaprasad; Wadkar, Kuntinath; Ingle, Nilesh; Gairola, Sunil; Dhere, Rajeev; Koide, Fusataka; Grimes, Sheila
Highlights: Neurovirulence, viscerotropism and immunogenicity were evaluated in monkeys. Neurovirulence and viscerotropism scores were lower than Stamaril. Complete seroconversion was observed by day 14 post inoculation. Clinical and histological scores were comparable with WHO reference virus 168/73. Abstract: Yellow fever vaccine associated neurovirulence and viscerotropism have been reported by various countries. In this study, the neurovirulence, viscerotropism and immunogenicity of yellow fever vaccine seed lots (master and working) and final product manufactured at Serum Institute of India (SII) were evaluated in cynomolgus monkeys. WHO reference virus 168-73 and Stamaril™ as a control vaccine was used for comparison. Neurovirulence and viscerotropism scores of the seed lots and final product were lower than Stamaril™. The SII seed virus and vaccine complies to the WHO requirement for neurovirulence, viscerotropism and immunogenicity, when tested in comparison to WHO reference seed virus 168/73. All challenged animals showed 100 % seroconversion as early as day 14 and neutralizing antibody titers were sustainable at day 30 in all animals.